SISTEM PENDIDlKAN NASIONAL DALAM TANTANGAN - Anita Lie (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2013)
Two items appear at the horizon when looking atthe highly productive population of this country: hope and challenge. On the one hand, a high percentage of young people inspires hope of productivity, creativity and innovation. On the other hand, we see the challenges of reducing unemployment and developing the quality of our human resource. Fulfilling the needfor quality basic education and health services of the people is required to be able to face this challenge. There are three basic problems with respect to systems and policies of national education in Indonesia: (1) there is a tug-of-war between centralization and decentralization as regards systems and policies; (2) there is a need to provide quality education to everyone and for everyone; and (3) Clarity of goals: for whom is this education? And on whose side is national education on? Any choice of national policy for the educational system must orient educational practice at the national level while at the same time appreciating the value of local wisdom and taking into consideration the variety of backgrounds that the people may have. There needs to be good will among public education policy makers at the national and regional levels to the point of even inviting representatives from teachers at the local level to participate in the making of the curriculum, asking them to be involved in the management of the educational process, soliciting their help in the implementation of the plan at all levels, asking them to assist in the periodical assessments and following them up on it. These teachers should, in fact, be and actually are at the frontline of the effort to provide a national policy for the system of education and should be actively involved in its implementation. Any educational system should aim at the eradication of poverty from society and, at the same time, out of justice, to provide education to everyone andfor everyone. These principles really need to be followed considering the variety of the situations of people who are living in Indonesia.